Feedback regulation in cell signalling: Lessons for cancer therapeutics. (February 2016) - Nguyen, Lan K.; Kholodenko, Boris N.
Highlights: Concept of feedback is fundamental for the understanding of signal transduction. Feedbacks bring about adaptation, robustness and complex dynamic behaviours. Hidden feedback is generated by protein-protein interactions in signaling cascades. Drug resistance often occurs due to drug-induced perturbations to feedback control. Design of effective drug combinations needs taking into account feedback regulation. Abstract: The notion of feedback is fundamental for understanding signal transduction networks. Feedback loops attenuate or amplify signals, change the network dynamics and modify the input-output relationships between the signal and the target. Negative feedback provides robustness to noise and adaptation to perturbations, but as a double-edged sword can prevent effective pathway inhibition by a drug. Positive feedback brings about switch-like network responses and can convert analog input signals into digital outputs, triggering cell fate decisions and phenotypic changes. We show how a multitude of protein–protein interactions creates hidden feedback loops in signal transduction cascades. Drug treatments that interfere with feedback regulation can cause unexpected adverse effects. Combinatorial molecular interactions generated by pathway crosstalk and feedback loops often bypass the block caused by targeted therapies against oncogenic mutated kinases. We discuss mechanisms of drug resistance caused by network adaptations and suggest that development of effective drug combinations requires understanding of how feedback loops modulate drug responses.